A review of participatory modelling techniques for energy transition scenarios - Jair K.E.K. Campfens; Mert Duygan; Claudia R. Binder (Advances in Applied Energy)
Energy transitions are pivotal for sustainability, yet their complexity and uncertainty pose significant challenges for effective planning and implementation. Participatory modelling has emerged as a promising approach to support these transitions, as it involves incorporating stakeholders' perspectives into models and policy designs, which helps integrate their mental models and preferences into simulations. This paper reviews the current state of participatory modelling in transition research for energy scenarios. Drawing on a comprehensive literature review and semi-structured interviews, we extract findings by evaluating participatory modelling techniques against criteria such as normative dimensions, non-linearity, actors and agency, uncertainty and emergence. Findings reveal that techniques like Cross-Impact Balance analysis and Fuzzy Cognitive Mapping excel in incorporating normative aspects and capturing diverse actor perspectives, yet they face challenges in addressing non-linearity and uncertainty. Bayesian Networks and Agent-Based Models are strong in managing uncertainty and modelling emergent behaviours but show limitations in normative aspects. Our findings provide a foundation for scholars and practitioners in the field of socio-technical energy transitions to select participatory modelling techniques best suited to their specific research contexts. This review also highlights gaps between theoretical potential and practical application of participatory modelling techniques. Bridging these gaps requires methodological advancement and a more rigorous application in empirical studies. To this end, future directions for blending techniques are discussed to better address the complexities of energy transitions.